TÌM ĐIỀU KIỆN TỐI ƯU CHO QUÁ TRÌNH TRÙNG HỢP POLYME ƯA NƯỚC TRÊN CƠ SỞ AXIT ACRYLIC SỬ DỤNG CHẤT KHƠI MÀO AMONI PESULFAT BẰNG PHƯƠNG PHÁP QUY HOẠCH HÓA THỰC NGHIỆM - Công, Trịnh Đức; Khôi, Nguyễn Văn (Vietnam Journal of Science and Technology, 2012)
DETERMINATION FOR OPTIMUM CONDITION OF POLYMERIZATION OF WATER-SOLUBLE  BASED ON ACRYLIC ACID USING AMONIUM PERSULFATE AS INITIATOR BY EXPERIMENTAL OPTIMIZATION The polymerization of acrylic acid in aqueous solution using ammonium persulfate as initiator was studied by experimental optimization method. The optimum factors are determined by MODDE 5.0 software. The results show a perfect and reliable fit with experimental verification.